2000
DOI: 10.1021/bi000498h
|View full text |Cite
|
Sign up to set email alerts
|

Specific Binding of α-Macroglobulin to Complement-Type Repeat CR4 of the Low-Density Lipoprotein Receptor-Related Protein

Abstract: The low-density lipoprotein receptor-related protein (LRP) is a large surface receptor that mediates binding and internalization of a large number of structurally and functionally unrelated ligands. The ligand binding sites are located in clusters of complement-type repeats (CR), where the general absence of mutual binding competition suggests that different ligands map to distinct sites. Binding of alpha(2)-macroglobulin-protease complexes to the LRP is mediated by the receptor binding domain (RBD) of alpha(2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
27
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 35 publications
7
27
0
1
Order By: Relevance
“…These receptors are transported through the ER-Golgi secretory pathway bound to the receptor-associated protein RAP (LRPAP1 or 2-macroglobulin receptor-associated protein) that acts as a chaperone and presumably protect receptors from early binding to ligands until dissociation occurs at the lower pH in later Golgi compartments (39). Studies with E. coli produced LA modules without glycans established that RAP binds to multiple LA modules through electrostatic interaction between three calcium-coordinating acidic residues in each LA and lysine residues (9, [40][41]. In LRP1 the most juxtamembrane cluster of LA modules LA3-6 that contains linker O-glycans ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…These receptors are transported through the ER-Golgi secretory pathway bound to the receptor-associated protein RAP (LRPAP1 or 2-macroglobulin receptor-associated protein) that acts as a chaperone and presumably protect receptors from early binding to ligands until dissociation occurs at the lower pH in later Golgi compartments (39). Studies with E. coli produced LA modules without glycans established that RAP binds to multiple LA modules through electrostatic interaction between three calcium-coordinating acidic residues in each LA and lysine residues (9, [40][41]. In LRP1 the most juxtamembrane cluster of LA modules LA3-6 that contains linker O-glycans ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, LRP1 may contribute to the sustained increase in intracellular calcium required for Pyk2 phosphorylation, probably because of the capacity of LRP1 to retain calcium in its fifth and sixth CR-domain (CR56). 45 Moreover, our results showed that hypoxia-induced LRP1 overexpression is linked to Pyk2 phosphorylation and MMP-9 activation in hVSMC. In accordance, LRP1 deficiency prevented hypoxia-induced MMP-9 overexpression, and that both LRP1 and MMP-9 silencing delayed hypoxiainduced hVSMC migration.…”
Section: Discussionmentioning
confidence: 58%
“…With Golgi being the site for initiation of GalNAc-type O-glycosylation it is possible that O-glycosylation plays a role in the interaction with RAP. RAP binding to LDLR and its related receptors occurs via the LDLR class A repeats overlapping several of the O-glycan sequence motifs described here (9,10). Curiously, RAP itself is also O-glycosylated at several sites (19), two of which are in the RAP-D3 domain, the major domain participating in LDLR binding (57).…”
Section: Discussionmentioning
confidence: 96%